Emerging Scholar Profile: Dr. Yana Wengel (e-Review of Tourism Research, 2018)
Dr. Yana Wengel is a critical tourism scholar with research interests revolving around volunteer tourism, non-profit tourism, sustainable development, and creative methodologies. Currently, Yana is a Post Doctoral Research Fellow at the Leeds Beckett University, UK. She works at the International Centre for Research in Events, Tourism and Hospitality (ICRETH) in the "Tourism in Times and Places of Turmoil" project.In 2017, Yana was awarded a Ph.D. from the University of Waikato in New Zealand. Her research project examined the experiences of farmers and volunteers (‘WWOOFers') in the Worldwide Opportunities on Organic Farms (WWOOF) programme. In tourism studies, the WWOOF programme has been framed as an alternative form of tourism that networks people interested in participating in sustainable lifestyles on organic farms. Using qualitative methods, that privileged participants' voices, the research found that farmers and WWOOFers socially construct their experiences through being involved in ‘dirty activities', crossing various thresholds, and striving for personal ideals (Wengel, McIntosh, & Cockburn-Wootten, 2018). The findings of Yana’s research challenge the idealistic aims of volunteer tourism exchange programmes that are usually reported in tourism literature and provides a further understanding of the experiences that shape the image of non-profit tourism exchange programmes.With the aim to introduce creative and innovative tools to a methodologically often traditional landscape in the academic field of tourism, Yana’s research employed both LEGO® SERIOUS PLAY® (LSP) and Ketso methodologies. Since then, Yana endeavours to inspire fellow academics about the potential use of LSP and Ketso in tourism research during conferences and workshops. Yana used LSP methodology as a tool to construct tourism realities through models made of Lego bricks and their metaphorical explanations created by research participants (Wengel, McIntosh, & Cockburn-Wootten, 2016). Additionally, Yana proposes Ketso as a useful creative tool for qualitative data analysis, which can enhance the clarity of the outcomes produced through thematic analysis. Overall, Yana’s research contributes to a greater understanding of the social construction of tourists’ experiences, and it further makes methodological contributions to the field.Yana has an emerging record of publishing in top-ranked refereed international journals, such as Annals of Tourism Research, Journal of Hospitality and Tourism Management, and Hospitality & Society, and many conference presentations and workshops. Also, she serves as an ad-hoc reviewer for Tourism Management, Current Issues in Tourism, Journal of Sustainable Tourism, Hospitality and Society, Rural Sociology and is a board member of the Journal On Tourism and Sustainability.Yana embodies the international outlook of her field of research and tourism more generally, having studied, taught and conducted research in Russia, Germany, New Zealand, Nepal, Myanmar, and the UK. Yana did her postgraduate studies in Tourism Development Strategies (M.A.) and Renewable Energy (PGCert) in Germany. She has been invited as a visiting academic to Glasgow University, Kathmandu University and National Management Business College in Myanmar. Yana has thus been able to build up extensive experience in teaching tourism and business subjects at both undergraduate and postgraduate levels to students from a variety of cultural backgrounds. Dedicated to providing a high-quality experience to her students, she obtained the 1st level of the Postgraduate Certificate in Tertiary Teaching and additionally trained as a Ph.D. Supervisor.Several successful grant applications for external funding further support the current importance of Yana’s research. She received grants from the University of Waikato, Trust Waikato, Community Waikato and DAAD - German Academic Exchange. Additionally, she was awarded the Waikato Management School’s Outstanding Doctoral Student Award in 2015. In terms of leadership, she held senior roles within the department at the Mandalar Degree College and Waikato University students’ organisations.Yana’s research and expertise are relevant and valuable to the industry. As certified LEGO® Serious Play® facilitator and Ketso practitioner, she has gained broad consulting experience for a variety of clients. In 2018, she served as an external advisor to Nepal Association of Rafting Agents (NARA) and Nepal Association of Tour & Travel Agents (NATA) members on developing the “Interaction programme on Tourism Policy and Tourism Infrastructure Development” and “Visit Nepal 2020” campaign. In 2016-2017, she worked for the LuxDev Aid and Development agency in Myanmar as part of the "HR Development in Hospitality and Tourism Sector" project. Yana further has been involved in a number of community projects and held seminars and workshops using LSP and Ketso. Dedicated to applying her knowledge and expertise to the benefit of communities, she has volunteered as a scout leader and refugee settlement support volunteer for the New Zealand Red Cross. She also assisted in the building of a successful network that endeavours to link communities and the world of research in New Zealand.Yana's future research agenda is linked to the postdoc project "Tourism in Times and Places of Turmoil", led by Professor Dorina- Maria Buda. This project investigates tourism in times and places of on-going socio-political turmoil and conflicts. In particular, Yana is involved in interdisciplinary research focused on the interconnections between tourist spaces, people and emotions in times and places of socio-political conflict. Her future research includes continued development of the use of creative methodological tools in tourism, and sustainable development in Asia through tourism.In her free time, Yana enjoys outdoors, tramping and climbing. In 2017, she organised an expedition to Mera Peak in Nepal. Yana also enjoys crafts, plays Lego seriously with her son and enjoys practising her (four) languages and learning new ones.ReferencesWengel, Y., McIntosh, A., & Cockburn-Wootten, C. (2018). Tourism and ‘dirt’: A case study of WWOOF farms in New Zealand. Journal of Hospitality and Tourism Management, 35, 46-55. https://doi.org/10.1016/j.jhtm.2018.03.001Wengel, Y., McIntosh, A. J., & Cockburn-Wootten, C. (2016). Constructing tourism realities through LEGO® SERIOUS PLAY®. Annals of Tourism Research, 56, 161-163. http://dx.doi.org/10.1016/j.annals.2015.11.012